2009
DOI: 10.1002/chem.200900615
|View full text |Cite
|
Sign up to set email alerts
|

COMU: A Safer and More Effective Replacement for Benzotriazole‐Based Uronium Coupling Reagents

Abstract: We describe a new family of uronium-type coupling reagents that differ in their iminium moieties and leaving groups. The presence of the morpholino group in conjunction with an oxime derivative--especially ethyl 2-cyano-2-(hydroxyimino)acetate (Oxyma)--had a marked influence on the solubilities, stabilities, and reactivities of the reagents. Finally, the new uronium salt derived from Oxyma (COMU) performed extremely well in the presence of only 1 equiv of base, thereby confirming the effect of the hydrogen bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
296
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 276 publications
(306 citation statements)
references
References 98 publications
6
296
2
2
Order By: Relevance
“…Prenylated and cysteine O-methylated peptides, labeled at their N terminus with a fluorescent S-bimanylthioacetyl residue, were synthesized using solution-phase methods as described previously (10,11,48,49). Briefly, Fmoc-FFC(trityl)-OMe, Fmoc-GGC (trityl)-OMe, and Fmoc-AAC(trityl)-OMe were first synthesized (via the appropriate dipeptide derivatives) from the appropriate Fmoc amino acids and S-tritylcysteine O-methyl ester, using (1-cyano-2-ethoxy-2-oxoethylidenaminooxy)dimethylaminomorpholinocarbenium hexafluorophosphate (COMU) as coupling reagent (50), and then S-deprotected with trifluoroacetic acid/triethylsilane (96/4 vol/vol, 1 h, 25°C) and S-prenylated using farnesyl or geranylgeranyl bromide (10). The resulting prenylated tripeptides were extended to pentapeptides by further cycles of Fmoc deprotection and COMU-mediated coupling, using γ-2-phenylisopropyl and 4-methyltrityl protection for the side chains of glutamic acid and lysine residues, and then Fmoc deprotected and labeled on their N termini with the succinimidyl ester of S-bimanylthioacetic acid (10).…”
Section: Methodsmentioning
confidence: 99%
“…Prenylated and cysteine O-methylated peptides, labeled at their N terminus with a fluorescent S-bimanylthioacetyl residue, were synthesized using solution-phase methods as described previously (10,11,48,49). Briefly, Fmoc-FFC(trityl)-OMe, Fmoc-GGC (trityl)-OMe, and Fmoc-AAC(trityl)-OMe were first synthesized (via the appropriate dipeptide derivatives) from the appropriate Fmoc amino acids and S-tritylcysteine O-methyl ester, using (1-cyano-2-ethoxy-2-oxoethylidenaminooxy)dimethylaminomorpholinocarbenium hexafluorophosphate (COMU) as coupling reagent (50), and then S-deprotected with trifluoroacetic acid/triethylsilane (96/4 vol/vol, 1 h, 25°C) and S-prenylated using farnesyl or geranylgeranyl bromide (10). The resulting prenylated tripeptides were extended to pentapeptides by further cycles of Fmoc deprotection and COMU-mediated coupling, using γ-2-phenylisopropyl and 4-methyltrityl protection for the side chains of glutamic acid and lysine residues, and then Fmoc deprotected and labeled on their N termini with the succinimidyl ester of S-bimanylthioacetic acid (10).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, El-Faham and Albericio [25][26] reported the new additives as well as their uronium salts derivatives as replacement for HOBt and HOAt derivatives (Figures 3 and 4). Among these entire additives Oxyma [26] (Figure 3) and its uronium salt COMU (Figure 4) showed an excellent replacement for HOBt and its analogues [26,27]. synthesis [27].…”
mentioning
confidence: 99%
“…Among these entire additives Oxyma [26] (Figure 3) and its uronium salt COMU (Figure 4) showed an excellent replacement for HOBt and its analogues [26,27]. synthesis [27]. Oxyma-B, has the same structure future for the carbonyl moiety in which the oxime group is flanked between the two carbonyl group as in HONM.…”
mentioning
confidence: 99%
“…Oxyma can be handled with considerably lower risk than the explosive benzotriazole, as determined by calorimetric techniques. 36,37) In the hope of suppressing the loss of chiral integrity during stepwise coupling and enhancing the coupling yield, 1-hydroxypyridin-2(1H)-one 3 and ethyl 2-cyano-2-(hydroxyimino)acetate 4 (oxyma) are used to replace HOBt 1 and HOAt 2. The reactivity of the sulphonate esters is expected to be directly related to the stability of the leaving group anions (OBt Ϫ , OAt Ϫ , PyO Ϫ and CNOEtO Ϫ ), and accordingly related to their pK a values.…”
mentioning
confidence: 99%
“…Oxyma displayed a remarkable capacity to inhibit racemization, together with impressive coupling efficiency, in both automated and manual synthesis, superior to those of HOBt and at least comparable to those of HOAt. [36][37][38] Stability assays showed that there was no risk of capping the resin under standard coupling conditions. Oxyma can be handled with considerably lower risk than the explosive benzotriazole, as determined by calorimetric techniques.…”
mentioning
confidence: 99%